Bleeding from jejunal varices formed at the Roux-en-Y jejunum site caused by the compression of the left renal vein after living donor liver transplantation with renoportal anastomosis - Wataru Nakanishi; Shigehito Miyagi; Kazuaki Tokodai; Atsushi Fujio; Toshiaki Kashiwadate; Kengo Sasaki; Yoshihiro Shono; Mineto Ohta; Yoshikatsu Saitoh; Michiaki Unno; Takashi Kamei (Surgical Case Reports, 2021)
Abstract Background Renoportal anastomosis is an option for the portal vein reconstruction of a liver transplantation with grade 4 portal vein thrombosis and a splenorenal shunt. Here, we report the case of gastrointestinal bleeding who underwent living donor liver transplantation (LDLT) with renoportal anastomosis. Case presentation Six-year-old female patient who underwent LDLT with renoportal anastomosis at 1 year of age had severe anemia with normal liver function during the follow-up period. The varices at the Roux-en-Y jejunum were considered the source of bleeding, and the compression of the left renal vein, which is known as a cause of Nutcracker syndrome, seemed to induce venous hypertension through the splenorenal shunt, which might induce the formation of the varices. She underwent percutaneous transhepatic sclerotherapy of the varices, and the anemia improved at her last follow-up, 6 months after sclerotherapy. This is the first reported case of Roux-en-Y jejunal varices bleeding related to the compression of the left renal vein after LDLT was performed with renoportal anastomosis. Conclusions Although renoportal anastomosis should be cautiously performed when there are no options for severe portal vein thrombosis, the status of the left renal vein and new collateral formation should be observed carefully during the follow-up period in pediatric cases of renoportal anastomosis.